Building a Pediatric Perioperative Surgical Home: One Patient, One Team. Issue 2 (April 2018) - Robinson, Renee; Schriefer, Jan; Gloff, Marjorie; Michels, Julie; Webber, Audra; Hilt, Suzanne; Sanders, James; Herman, Emily
Abstract : Introduction: The pediatric perioperative surgical home (PPSH) is a population health management model designed to provide a seamless experience for children and their families undergoing surgical procedures. The purpose of this quality improvement project is to evaluate the feasibility and utility of implementing a PPSH at an academic medical center. Method: A multidisciplinary team was formed, composed of representatives from nursing, surgery, anesthesiology, and perioperative medicine. This group developed a comprehensive preoperative screening tool designed for early identification of patient barriers before elective surgery. The screening tool was developed with input from multiple pediatric subspecialists. At the initial surgical visit, patients and families are encouraged to complete this screening tool. The screening tool was piloted to 74 patients (46 completed) in a pediatric orthopedic clinic for an 8-month period. Existing tools in the electronic medical record system were identified to assist with care coordination perioperatively. Result: In comparing our baseline period (2016, n = 174) with the early implementation phase of our PPSH (2017, n = 188), unplanned readmission rates decreased from 4.0% to 2% ( p = .011), and surgical site infections decreased from 3.5% to 2.3% ( p = .002), whereas unplanned return to operating room and average length of stay remained the same. Conclusion: Information obtained within a PPSH informs the entire team of important factors that could influence perioperative care. A PPSH serves to make the health care team more efficient and may also be associated with a reduction in complications, cost, and time spent in the hospital.